Maternal health services utilization and its contributing factors among adolescent mothers - Dewi Nuryana; Pramon Viwattanakulvanid; Nohan Arum Romadlona (Intelektual Pustaka Media Utama, 2022)
Adolescent girls (15-19 years old) experienced childbirth face the higher risk for maternal mortality than older women. This study aimed to assess the utilization level of maternal health services and to identify factors that contribute to the maternal health services utilization in Indonesian adolescent mothers. The study used secondary data from 2017 Indonesia Demographic and Health Survey (IDHS) and included women who had last birth at the age of 15-19 years old which total is 866 women. Among adolescent mothers, the highest level of utilization is post-natal care (PNC) (71.5%) followed by antenatal care (ANC) (67.2%) then delivery services (64.5%). Factors that associated with ANC utilization are husband/partner’s education, mother’s autonomy, region, husband accompanied during ANC, topic discussed during ANC, and intendedness of last birth (p<0.05). Factors contributed to delivery services are mother’s education, mother’s working status, mother’s autonomy, residence, region, wealth index, health insurance, husband accompanied during ANC, and topic discussed during ANC (p<0.05). Whereas, for PNC utilization are knowledge of danger sign during childbirth, residence, region, and delivery services utilization (p<0.05). Therefore, health strategic programs which focused on adolescent mothers are necessary to improve the maternal health in Indonesia.